Study of serum cholinesterase, CPK and LDH as prognostic biomarkers in organophosphorus poisoning - Rajdip Sen; Jadumani Nayak; Sagar Khadanga (International Journal of Medical Research and Review, 2014)
Introduction: Organophosphorus insecticides are arguably one of the commonest causes of morbidity and mortality due to poisoning worldwide, especially in developing countries like India due to its easy availability. This study was conducted to estimate the levels of Serum Cholinesterase, Serum Creatinine Phosphokinase & Serum Lactate Dehydrogenase on admission for correlation with severity of organophosphate poisoning and to reevaluate their levels on Day 4 and Day 8 and correlate them with the complications and final outcome of the poisoning.Material and methods: This is a single centered cross sectional study over a period of one year.100 patients of OP poisoning were selected and their clinical severity was categorized according to Peradeniya organophosphorus poisoning (POP) scale. Level of serum Cholinesterase, serum CPK, and serum LDH were measured at admission and on Days 4 and 8.Results: Serum Cholinesterase and CPK levels strongly correlated with clinical severity. The comparative values of serum Cholinesterase and serum LDH amongst survivors and non survivors during the course of the study was not statistically significant. The comparative values of serum Creatinine Phosphokinase between survivors and non survivors showed a statistically significant difference.Conclusion: Serum Cholinesterase serves as a diagnostic parameter for organophosphorus poisoning and correlates with the severity but it cannot be used as a prognostic biomarker. Serum Creatinine Phosphokinase shows a strong degree of positive correlation with the severity of poisoning and can be used as a predictor of outcome in organophosphorus poisoning.